Existence of nanoparticles in azurite and malachite pigments – Raman spectroscopy and X-ray diffraction studies. (October 2016) - Han, Kiok; Nam, Ji-Yeon; Ji, Jeong-Eun; Kang, DaiIll; Lee, Hanhyoung; Baek, Nayeon; Song, Youna; Yang, In-Sang
Abstract: The lightness of the color of mineral pigments changes with its particle size. We investigated the Raman spectra of azurite pigments of several particle-size groups, ranging from ∼5 to ∼110 μm. The line-widths of the phonon modes ∼400 cm −1 of azurite powders were found to increase as the particle sizes get smaller. Similar phenomena were also observed for the malachite pigments. The broadening of phonon modes implies the existence of nanoparticles in the pigment powder. Scanning Electron Microscopy (SEM) measurements confirm the existence of more nanoparticles in the finer particle-size groups. These results were assured by X-ray diffraction (XRD) measurements as well. Even further, we could determine the average size of azurite particles simply by comparing the line-width of the Raman mode ∼400 cm −1 of the unknown with that of the known particle-size groups. Non-destructive estimation of typical sizes of mineral pigments using Raman spectroscopy could be useful in cultural-heritage conservation science. Highlights: Raman spectra of azurite and malachite pigments show line-broadening for fine grains. Existence of more nanoparticles in the finer particle-size groups is supported by SEM and XRD. The average size of azurite particles is determined easily by the line-widths of the Raman modes.